Public Debt and Economic Growth: Is There Any Causal Effect? An Empirical Analysis With Structural Breaks and Granger Causality for Jordan - Omar Kasasbeh (Asosiasi Dosen Akuntansi Indonesia, 2021)
Public debt in Jordan raised because of fiscal expansions. This study investigates whether public debt contributed to the economic growth in Jordan over the period 1980 to 2020. It also investigates whether other indicators of the debt burden, such as external debt service, budget expenditure, and budget deficit, have an influence on economic growth. The results of this study are harmonic with the extant literature that found an inverse relationship between debt burden and growth. The study found that the public debt over time has a negative impact on GDP